Valuasi Ekonomi Sumberdaya Terumbu Karang di Kawasan Konservasi Gita Nada - Sekotong - Hilyana, Sitti; Amir, Sadikin; Buhari, Nurliah; Waspodo, Saptono; Gigentika, Soraya (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
Economic valuation is an important instrument in making policies for managing coral reef resources effectively and efficiently and is able to distribute the value of benefits and costs in developing conservation areas. This study aims to determine the economic valuation of coral reef resources in TWP Gita Nada Sekotong Lombok Barat Regency. The research used the survey method with a sample size of 45 respondents determined by purposive random sampling based on the status of the respondent. Data analysis uses the Total Economic Value (TEV) approach by aggregating the value of direct benefits, indirect benefit values, value of selected benefits, value of existence benefits, and value of inheritance benefits. The results showed that the TEV of coral reef in TWP Gita Nada was Rp. 147,976,915,107.98/year or IDR 54,778,806.30/ha/year. The value of indirect benefits contributed IDR 113,523,601,904.00 per year (76.7% of the total economic value of coral reefs), while the direct benefit contributes Rp. 34,453,313,203.98 per year (23.3% of the total economic value of coral reefs).